2018
DOI: 10.1634/theoncologist.2017-0578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant pH-Elevating Medications with Pazopanib on Progression-Free Survival and Overall Survival in Patients with Metastatic Renal Cell Carcinoma

Abstract: Pazopanib is a preferred category-one first-line treatment for predominant clear cell metastatic renal cell carcinoma (mRCC). However, because of an aging demographic, coupled with patients with mRCC presenting with multiple comorbidities, including symptomatic dyspepsia or gastroesophageal reflux disease, patients are commonly required to take pazopanib concomitantly with a proton pump inhibitor (PPI) or a histamine 2 receptor antagonist (H2RA). Despite earlier pharmacokinetic reports suggesting that an alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
5
25
0
Order By: Relevance
“…Two studies reported shorter PFS and overall survival (OS) in patients treated with pazopanib receiving concomitant pH‐elevating medication, though in one of these studies the effect on treatment outcome was not statistically significant . Unfortunately, no pazopanib plasma concentrations were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported shorter PFS and overall survival (OS) in patients treated with pazopanib receiving concomitant pH‐elevating medication, though in one of these studies the effect on treatment outcome was not statistically significant . Unfortunately, no pazopanib plasma concentrations were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies reported shorter PFS and overall survival (OS) in patients treated with pazopanib receiving concomitant pH-elevating medication, though in one of these studies the effect on treatment outcome was not statistically significant. 148,149 Unfortunately, no pazopanib plasma concentrations were measured. However, considering the essential role of gastric pH in the absorption of pazopanib and the previously established decrease in pazopanib AUC when combined with a proton pump inhibitor, it is likely that the shortened survival is caused by underexposure to pazopanib.…”
Section: Gastric Phmentioning
confidence: 99%
“…A total of 353 potentially eligible records were identified in the electronic databases. After exclusion of n=337 not pertinent papers, n=16 were selected for inclusion in quantitative analysis (n=372,418 patients included, with 12% of patients receiving concomitant GAS therapy) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The search results and characteristics of the included studies are presented in figure 1 and tables 1-2.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 353 potentially eligible records were identified in the electronic databases. After exclusion of n=337 not pertinent papers, n=16 were selected for inclusion in quantitative analysis (n=372,418 patients included, with 12% of patients receiving concomitant GAS therapy) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] All studies were retrospective except for a pooled analysis of phase 2-3 studies by Lalani et al and a secondary analysis of a randomized prospective trial by Chu et al Oncologic treatment consisted in oral TKIs in n=11 studies, while in n=4 studies patients received oral chemotherapy (i.e. capecitabine); one study did not include information regarding the type of study drugs.…”
Section: Resultsmentioning
confidence: 99%